2019
DOI: 10.1080/10749039.2019.1612438
|View full text |Cite
|
Sign up to set email alerts
|

Transvlogs: online communication tools for transformative agency and development

Abstract: This paper examines how 21 transgender individuals used YouTube transvlogs to co-create their own transformative agency. Drawing on a social justice framework, I conduct narrative content analysis to explore how a historically marginalized population enacted their own transformative development without researcher intervention. I suggest that by questioning the status quo, explicating and envisioning new activity patterns, and committing to concrete online and offline actions, transvloggers develop themselves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…While choices around online visibility are crucial for all LGBTQ+ people, the importance of these spaces is more pronounced for trans people [21,35,57]. In response to these experiences and with the awareness that trans experiences differ significantly from larger LGBTQ+ experiences, HCI scholars have begun to shift the focus of social media research towards the specific experiences of trans people (e.g., [28][29][30][31]56]).…”
Section: Transgender Identity Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…While choices around online visibility are crucial for all LGBTQ+ people, the importance of these spaces is more pronounced for trans people [21,35,57]. In response to these experiences and with the awareness that trans experiences differ significantly from larger LGBTQ+ experiences, HCI scholars have begun to shift the focus of social media research towards the specific experiences of trans people (e.g., [28][29][30][31]56]).…”
Section: Transgender Identity Onlinementioning
confidence: 99%
“…Participants' processes of coming out frequently followed a trajectory composed of several distinct disclosures across their social media ecosystems. Previous work has demonstrated that online spaces are important for LGBTQ+ (e.g., [24]) and specifically for trans people to find information and support (e.g., [21]). Our participants' experiences echo these findings, as they told us that they often came to better understand their trans identities in the spaces that they had curated within social media platforms.…”
Section: Disclosing Across Social Media Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study contributes to previous work on the resilience benefits of online trans communities (i.e., Craig et al, 2015;Etengoff, 2019;Singh, 2013) by expanding the scope of psychological inquiry from online media content creators to include online media viewers. Given Craig et al's (2015) stance that LGBTQ + individuals' choice to engage online media is an act of resilience, proactive coping, and resource management, this study approached transvlog viewer engagement as a gateway to self and relational resilience pathways.…”
Section: Discussionmentioning
confidence: 88%
“…For trans individuals facing social rejection and discrimination, trans community engagement, both online and offline, can promote feelings of visibility, belonging, inspiration, and self‐acceptance (Paceley et al, 2020 ; Puckett et al, 2019 ). Although several studies have analyzed the benefits of trans individuals creating online video blogs (Etengoff, 2019 ; Horak, 2014 ; Raun, 2015a , 2015b ), there is a dearth of research exploring trans video blog viewers' experiences. However, trans online video blogs, otherwise known as transvlogs, are inherently interactional, as viewers and creators dialog via comment forums and video responses (Etengoff & Rodriguez, 2016 ; Etengoff, 2019 ; Rotman & Preece, 2010 ).…”
Section: Introductionmentioning
confidence: 99%